Faktor-Faktor Yang Mempengaruhi Efisiensi Belanja Daerah Pemerintah Kabupaten/Kota Di Sumatera Selatan - Aznurita, Cahya; Sulaiman, Sulaiman; Indriasari, Desi (CV. ITTC INDONESIA, 2024)
This research aims to determine the influence of PAD Effectiveness and Regional Financial Independence Ratio on Regional Expenditure Efficiency of Regency/City Governments in South Sumatra in 2018-2022. The population in this study was 17 regencies/cities in South Sumatra with a total sample data of 85 Regency/City Government APBD Realization Reports in South Sumatra. Testing this hypothesis uses Multiple Linear Regression with the help of SPPS 26 software. The results of this research show that partially PAD Effectiveness and the Independence Ratio have a significant positive effect on regional spending efficiency. Simultaneously the effectiveness of PAD and the Independence Ratio together influence the efficiency of regional spending.